ANALISIS DETERMINAN PEMBIAYAAN BERMASALAH PADA BANK UMUM SYARIAH DI ASIA TENGGARA - Risna Febriyanti; Dadan Hamdani; Juliana Juliana; Rumaisah Azizah al-Adawiyah; Ropi Marlina (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Purpose -The purpose of this study is to examine the differences in non-performing financing and the factors that influence it in Islamic commercial banks in Southeast Asia, which include Islamic banks in Indonesia, Malaysia and Brunei Darussalam. Design / Methodology / Approach - The research method used is a comparative and verification method using panel data regression analysis using Eviews 9 software and SPSS. Findings - The results of the study indicate that the Return on Assets (ROA) variable has a negative and significant effect on non-performing financing, Operating Income Operating Expenses (BOPO) has no effect on non-performing financing, Gross Domestic Product (GDP) has a positive and significant effect and there are also differences in non-performing financing. in Islamic commercial banks in Southeast Asia. Practical Implications - Islamic commercial banks must consider various solutions and financing operations through analysis of both internal and external factors. For Islamic banks, it is very important to analyze through internal factors in order to avoid various problems caused by bank errors in financing distribution. In addition to internal factors, external factors can also affect non-performing financing. This external factor can be seen through the failure of the customer's business to do financing and also the unhealthy economic conditions. External factors are equally important to see the various behaviors that occur in customers. Originality / Value - This research is a research that is still rarely done because it not only examines the factors that affect non-performing financing but also looks at the differences in the non-performing financing of Islamic commercial banks in Southeast Asia, especially Indonesia, Malaysia, and Brunei Darussalam. Keywords: Non Performing Financing, Return on Assets, BOPO, Gross Domestic Product Paper Type: Research Paper